Perancangan Alat Analisis Kinerja Mesin Thimonnier, Takaran6, dan BIB pada PT. Smart, Tbk. - Jessi Gracea Maria (Jurnal Titra, 2020)
PT. Smart, Tbk. is a company that produces palm oil-based products. It produces product such as cooking oil, margarine, shortening, and specialty fats. Filling process is one of the process to putting oil in the package. The oil’s volume in the packaging is regulated under Weight in a Closed Package (BDKT) but on the other side, the company also has an oil loss budget. Oil loss is an amount of oil in a package that over the predetermined volume. The company expects the oil loss can be minimized by keeping the process on the machines that can be controlled and machines can have a good capability for each product. Dashboard is made to help to monitor and analyze the machine performance using SPC (Statistical Process Control) which consists of sigma level, control chart, and capability index. Further analysis is done by using eight control chart rules to find the possibility causes of the bad optimality. One of the causes of bad optimality is tool calibration. The calibration schedule for every machine must be determined. The results of the Dashboard state that most machines have suboptimal performance. In General, poor capability values can be caused by USL values that too optimistic.